Gµ-Closed Sets and Gm-Closed Sets in GTMS Spaces: Tatsanee Wiangwiset, Chokchai Viriyapong, Butsakorn Kong-ied - Team, Support (Thai Journal of Mathematics, 2017)
The main purpose of this article is to introduce the concepts of Gµ-closed sets and Gm-closed sets, which are a weak froms of closed sets in a generalized topology and minimal structure space. Some of their properties are studied. In particular, the characterizations of µmG-closed sets and µmG-closed sets are obtained using Gµ-closed and Gm-closed. Moreover, the notions of GT1- GTMS spaces and GT2-GTMS spaces are introduced.